Criticising the Abraham Geiger's Approach and Criticism of the Qur'an and the Prophet - Noor, Ahmad Yunus Mohd; Mokhtar, Asmilyia Mohd (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
The primary purpose of this paper is to explain the approach or method used by Abraham Geiger in criticizing the Qur’an and the Prophet Muhammad. This paper is essential to see the consistency of the approach and method of criticism that Geiger uses and how it influences perspectives in understanding the Qur’an and the Prophet Muhammad. Aside from being an Orientalist whom Judaism greatly influenced, Geiger was the first Western thinker to criticize the Qur'an and the Prophet Muhammad in his dissertation. Through document studies, this paper analyzes Geiger's point of view, who concludes that the Qur’an is a book adapted by the Prophet Muhammad from Judaism. This claim is scientifically criticized because it is not based on logical arguments and solid evidences. Even though Geiger's methodology is irrelevant, his influence is widespread. Furthermore, this paper introduces and criticizes Geiger's post-modern approaches, which continue the legacy, free thought ideas, and renew human life by refuting traditional Jewish, Christian, and especially Islamic teachings considered static and difficult to change.